2022
DOI: 10.3390/app12136577
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Morphological Study of the Saccharomyces cerevisiae Cell-Based Microcapsules with Novel Cold-Pressed Oil Blends

Abstract: Vegetable oils rich in polyunsaturated fatty acids are a valuable component of the human diet. Properly composed oil blends are characterized by a 5:1 ratio of ω6/ω3 fatty acids, which is favorable from a nutritional point of view. Unfortunately, their composition makes them difficult to use in food production, as they are susceptible to oxidation and are often characterized by a strong smell. Encapsulation in yeast cells is a possible solution to these problems. This paper is a report on the use of native and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
0
4
0
2
Order By: Relevance
“…Low-field NMR is a widely used method to describe the molecular properties of water in various biological samples, including food products [ 73 , 74 , 75 , 76 , 77 ]. The water in fresh pasta can be associated with the ingredients in the flour (starch, gluten), but also with added ingredients such as the sugars (in their various states) present in the kiwifruit.…”
Section: Resultsmentioning
confidence: 99%
“…Low-field NMR is a widely used method to describe the molecular properties of water in various biological samples, including food products [ 73 , 74 , 75 , 76 , 77 ]. The water in fresh pasta can be associated with the ingredients in the flour (starch, gluten), but also with added ingredients such as the sugars (in their various states) present in the kiwifruit.…”
Section: Resultsmentioning
confidence: 99%
“…When assessing the in vitro release of β-carotene in wheat germ oil encapsulated by alive, non-plasmolyzed, and plasmolyzed yeast cells, it was found that alive, non-plasmolyzed yeast cells exhibited a higher release rate under esophagus-stomach conditions. In contrast, plasmolyzed cells increased digestion in the duodenum and ileum [91].…”
Section: β-Carotenementioning
confidence: 88%
“…LF NMR is an emerging methodology in food analysis. It was applied for studying fats, gels, emulsions as well as tissue-structured products [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%